Systematic review and critical appraisal of child abuse measurement instruments. (February 2019) - Saini, Suriati Mohamed; Hoffmann, Cassandra R.; Pantelis, Christos; Everall, Ian P.; Bousman, Chad A.
Highlights: 15% of the child abuse instruments had strong to moderate levels of evidence. No instruments had adequate levels of evidence for all COSMIN criteria. No single instrument is superior to all others across settings and populations. Measures that capture the effects child abuse on brain development are limited. Abstract: Child abuse is a major public health concern and a strong predictor of adult psychopathology. However, a consensus on how best to measure child abuse is not evident. This review aimed to critically appraise the methodological quality and measurement properties of published child abuse measures, examined the strength of evidence of these instruments for research use using the COnsensus-based Standards for the selection of health Measurement InstrumeNts (COSMIN) checklist and determined which measures were capable of providing information on the developmental timing of abuse. Systematic search of electronic databases identified 52 eligible instruments from 2095 studies. Only 15% ( n  = 8) of the instruments had strong to moderate levels of evidence for three or more of the nine COSMIN criteria. No instrument had adequate levels of evidence for all criteria, and no criteria were met by all instruments. Our results indicate there is no single instrument that is superior to all others across settings and populations. The availability of measures capable of capturing the effects of child abuse on brain development and associated behavioral phenotypes are limited. Refined instruments with a focus on capturing abuse events during development are warranted in addition to further evaluation of the psychometric properties of these instruments.